2016
DOI: 10.1111/1751-2980.12342
|View full text |Cite
|
Sign up to set email alerts
|

Relevant risk factors for positive lateral margin after en bloc endoscopic submucosal dissection for early gastric adenocarcinoma

Abstract: Positive LM is closely related to the upper third of stomach, a tumor larger than 3 cm and a mixed-type carcinoma. Additionally, positive LM has a predilection for recurrent or residual tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Therefore, it can also provide some reference significance for endoscopists. Large tumors and proximal gastric location of EGCs have been reported as risk factors for non-curative ESD resection, 11,12,21,23,24 which are confirmed in our cohort. In this cohort, the results demonstrated large tumors were more likely to contain undifferentiated carcinoma components.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, it can also provide some reference significance for endoscopists. Large tumors and proximal gastric location of EGCs have been reported as risk factors for non-curative ESD resection, 11,12,21,23,24 which are confirmed in our cohort. In this cohort, the results demonstrated large tumors were more likely to contain undifferentiated carcinoma components.…”
Section: Discussionsupporting
confidence: 87%
“…20 Although there have been some studies focused on the relationship between tumor size, location and, ulcer and NCR, few studies explored other pre-procedural endoscopic findings for ESD treatment-related NCR in EGCs, not to mention eCura C1 and eCura C2 resections. 11 , 12 , 21 To minimize the risk of NCR and related unnecessary additional resection procedures, it is critically important for endoscopists to thoroughly evaluate the risk for NCR before any ESD procedure. The aim of this study was to identify clinically useful risk factors that may predict the risk of NCR, especially of eCura C1 and eCura C2 resections, before the start of an ESD procedure in EGC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al drew the conclusion through their research that positive margins with submucosal infiltration (odds ratio 3.6) and lymphovascular invasion (odds ratio 3.5) had significant correlation with lymph node metastasis and patients who didn't meet curative resection especially with lymphovascular invasion or positive margin with submucosal invasion should receive additional gastrectomy [31]. Positive lateral margin was related closely to a mixed-type carcinoma, larger than 3 cm in size and the upper one third of stomach, reported by Fu et al [32]. However, there is no research about the risk factor of vertical and lateral incomplete resection in EGCC patients which needs to study in depth.…”
Section: Discussionmentioning
confidence: 83%
“…Another Japanese study reported that the risk factors of positive horizontal margin were tumor size of >3 cm (odds ratio [OR], 1.794; p =0.029), tumor located in the upper third of the stomach (OR, 3.382; p =0.015), and mixed histological type (OR, 2.347; p =0.002) [23]. In a Korean study of 1358 ESD-treated patients with EGCa that aimed to identify the risk factors of positive horizontal margin, the authors concluded that extremely well-differentiated adenocarcinoma and multiple lateral margins were the only risk factors [24].…”
Section: Frequency and Risk Factors Of Positive Horizontal Marginmentioning
confidence: 99%